Effect of fruit maturity stage and fermentation period on the germination of passion fruit (Passiflora edulis f. flavicarpa Deg.) and sweet granadilla seeds (Passiflora ligularis Juss.) (2015)
In Colombia, we have found 165 species that belong to the Passiflora genus and, of these, about 50% have edible fruits. Among these, passion fruit, sweet granadilla and purple passion fruit are considered to be of economic importance. This study aimed to evaluate the effect of fruit ripeness and pulp fermentation time period (mucilage) on the seed germination of passion fruits (Passiflora edulis f. flavicarpa Deg.) and sweet granadillas (Passiflora ligularis Juss.) under laboratory conditions (alternating temperatures (30/20ºC, 12/12 hour), 60% relative humidity and in darkness for 60 days) and to establish growth parameters leaf area and plant dry mass. The seeds were extracted from fruits in three maturity stages (M4, M5 and M6) and five fermentation periods (0 days (F0);1 day (F1), 2 days (F2), 4 days (F4) and 8 days (F8)) using a completely random design with a 3x5 factorial arrangement (maturity stage x fermentation time), with four replicates of 50 seeds each. It was found that the M6F1 and M5F1 treatments were more favorable in terms of germination for the passion fruit (94.5 and 92.0%, respectively), while, for the sweet granadilla, the M6F2 (39%) and M6F1 (35%) treatments were more favorable. The growth parameters demonstrated that the highest dry mass value occurred in M6F8 for the passion fruit (136.76 mg) and in M6F1 for the sweet granadilla (104.73 mg); furthermore, these values increased as the maturity stage of the two species progressed. The leaf area of the passion fruit had maximum values in seedlings obtained from the treatment with maturity stage M5F2 and a fermentation period of 1 day, M5F2 (18.3 cm2), while the leaf area of the sweet granadilla increased in the same fashion as the dry mass, with M6F8 having the highest value (16.8 cm2).